Perubahan Fungsi Seni Lebon pada Masyarakat Desa Pepedan Kecamatan Parigi Kabupaten Pangandaran - Muhamad Ramdhani Khoerudin; Uus Karwati (Gondang: Jurnal Seni dan Budaya, 2019)
This study aims to obtain data on changes in function and initial forms of performing Lebon in the community, Pepedan Village, Parigi District, Pangandaran Regency. This study uses a qualitative descriptive approach. With the development of the current era through various factors, the Lebon art has turned into a means of entertainment that is arranged in such a way that the aim of the Lebon art remains sustainable and is accepted by the Papedan community. Lebon art in the language of the local community lebon has a meaning that is grave or buried. Lebon art performance can occur because there are two groups fighting over plantation land ownership or fighting over women to be wives, Lebon art is art that contains violence in earlier times, because in this art required as winners are surviving champions and losers must reach die and be buried in the place of the Lebon art performance. Lebon art in general Pangandaran community has become an art that was born originally from Pangandaran Regency.